FITRAH DALAM PERSPEKTIF AL-QURAN (KAJIAN TERHADAP AYAT-AYAT AL-QURAN) - Suriadi Suriadi (Universitas Muhammadiyah Ponorogo, 2018)
The religion of Islam as the religion of fitrah, is not only in accordance with the instinct of human religiosity, but also in accordance with even the development of its nature, including mansuia resources that will bring to its wholeness and personal perfection. This personal perfection which in Islamic education is called the human al-kamil, or perfect man. By nature, humans have found tauhid, though still in the immaterial realm (spirit realm). From that understanding, it can be understood that human nature is a tendency to know, or to seek God. This can be found in the consensus between God and the spirits who later became the general constitution. The consensus begins with God's question to the spirit, is not I your Lord? (they answer) surely you are our god, we are witnesses. Humans are creatures because they are influenced by innate (basic human potential) and environment. This is one of the essence of human being.